A comparison on the effects of Ultrasonic Scaling on the microleakage of class V composite resin and glass Ionomer cement restorations. - Yasini E; Rezvani MB (Tehran University of Medical Sciences, 2002)
Ultrasonic scaling of class V composite or glass Ionomer restorations may cause destructive effects. The purpose of this study is to investigate the effects of ultrasonic scaling on the marginal leakage of composite and Glass Ionomer restorations. An in-vitro study was performed on thirty- two upper and lower premolar teeth, free of any kind of caries, cracks or facets. Class V cavities, with the depth of 1.5 mm and the height and width of 2 mm, were prepared on the buccal and lingual surfaces. Occlusal margin and cervical margin were placed entirely in enamel and cementurn, receptively. Thirty-two cavities were restored with composite resin (Z100) (3M Co.), while the other thirty- two cavities were restored with Glass Ionomer cement (Vitremer) (3M Co.) and were bonded with Scotch Bond Multipurpose Plus (SBMP) (3M Co.). Half of each group were thermocycled, then half of each thermocyled and non-thermocycled groups were selected randomly for ultrasonic scaling test. After scaling, all teeth surfaces were coated with two layers of nail varnish up to 1mm of restoration. Samples were immersed in 0.5% fushin solution for 24 hours and were vertically sectioned by a diamond disk. Regarding dye penetration and microleakage, samples were examined by a stereobinoclar microscope. The results were analyzed by Mann-Whitney and Kruskal Wallis (a=0.05). They indicated that degree of microleakage in the composite/ enamel, with thermocycling and ultrasonic scaling were less than Glass Ionomer samples. Although in cervical margin, at the beginning, composite leakage was significantly less than Glass Ionomer cement, but thermocycling and ultrasonic scaling and their combination increased it and had a meaningful difference with Glass Ionomer.